The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages ii CONTENTS Introduction Page Nutritional requirements 1 Tables of nutritional values of rationed and unrationed foods Dietary rules and allowances for children aged 1 to 5 years 3 Dried Milk 4 General notes on daily meals 4 Breakfast, dinner, tea, sandwich fillings. Appendix I — Menus for 22 days 5 Specimen diet served at a Day Nursery 8 Appendix II — Recipes for 50 children aged two to five 8 Quantities of basic ingredients for separate meals 8 Soups: 1. Scotch Broth 2. Cottage Soup Meat Dishes: 3. Boiled Bacon 4. Braised Steak 5. Hot-pot 6. Irish Stew 7. Mince and Rice 8. Mince and Oatmeal Pudding 9. Mince Roly-poly 10. Baked Mutton 11. Sea Pie 12. Shepherds Pie 13. Stoved Potatoes 14. Bacon, Rice and Tomatoes Vegetarian Dishes: 15. Vegetable and Cheese Hot-pot 16. Potato and Lentil Pie Fish and Egg Dishes: 17. Scrambled Eggs 18. Creamed Eggs 19. Fish Cakes 20. Fish Pie 21. Stewed Fish 22. Sardines on Toast Vegetable Dishes: 23. Potatoes 24. Green Vegetables 25. Root Vegetables 26. Potato Pancake Puddings: 27. Castle Pudding 28. Chocolate Blancmange 29. Brown Betty 30. Sweet Twirls 31. Foundation Pudding 32. Milk Pudding 33. Chocolate Queen of Puddings 34. Cocoa Cap Custard 35. Fruit Charlotte 36. Semolina Whip Cakes and Biscuits : 37. Plain Cake 38. Oatmeal Biscuits 39. Oatmeal and Wheatmeal Scones 40. Crunch Miscellaneous : 41. Cocoa 42. Porridge 43. Rusks 44. Chocolate Spread 45. Mock Lemon Curd 46. Lentil Spread 47. Cream Cheese 48. Salads Appendix III. 17 (a) Medical Research Council's report on “The preservation of vitamins and salts in the preparation of green vegetables for the table.” (b) Practical rules for cooking green vegetables. 127/NU/5/5/1/28